In Vitro Pancreatic Lipase Inhibition by Marine Fungi Purpureocillium lilacinum Associated with Stylissa sp. Sponge as Anti-obesity Agent - Wendi Nurul Fadillah; Nampiah Sukarno; Dyah Iswantini; Min Rahminiwati; Novriyandi Hanif; Mashuri Waite (HAYATI Journal of Biosciences, 2022)
This study aimed to evaluate the potential of marine fungus Purpureocillium lilacinum isolated from an Indonesian marine sponge Stylissa sp. as an anti-obesity agent through pancreatic lipase inhibition assay. The fungus was identified as P. lilacinum through morphological and molecular characteristics. The fungal extract’s inhibition activity and kinetics were evaluated using spectrophotometry and Lineweaver-Burk plots. Ethyl acetate and butanol were used for extraction. Both extracts showed pancreatic lipase inhibition in a concentration-dependent manner. Both crude extracts were then fractionated once. All fractionated extracts showed inhibitory activity above 50%, with the highest activity found in fraction 5 of ethyl acetate at 93.41% inhibition. The best fractionated extract had an IC50value of 220.60 µg.mL-1. The most active fraction of P. lilacinum had a competitive-type inhibitor behavior as shown by the value of Vmax not significantly changing from 388.80 to 382.62 mM pNP.min-1, and the Michaelis-Menten constant (KM) increased from 2.02 to 5.47 mM in the presence of 500 µg.mL-1 fractionated extract. Metabolite identification with LC-MS/MS QTOF suggested that galangin, kaempferol, and quercetin were responsible for the observed lipase inhibition.